Molecular basis for PrimPol recruitment to replication forks by RPA - Thomas A. Guilliam (Nature Portfolio, 2017)
PrimPol is a multifunctional replicative enzyme that can bypass DNA damage, as well as reprime replication restart. Here, the authors have elucidated how PrimPol is recruited to stalled replication forks via specific interactions with RPA, which stimulates its primase activity.